2008
DOI: 10.1002/path.2302
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell‐based angiopoietin‐1 gene therapy for acute lung injury induced by lipopolysaccharide in mice

Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) can serve as a vehicle for gene therapy. Angiopoietin-1 (Ang1) is a critical factor for endothelial survival and vascular stabilization via the inhibition of endothelial permeability and leukocyte-endothelium interactions. We hypothesized that MSC-based Ang1 gene therapy might be a potential therapeutic approach for lipopolysaccharide (LPS)-induced lung injury. MSCs were isolated from 6 week-old inbred male mice and transduced with the Ang1 gene, using a lentiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
195
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(209 citation statements)
references
References 43 publications
12
195
1
1
Order By: Relevance
“…Unlike classical intravenous or intratracheal delivery methods [5][6][7][8][9] , intrapleurally delivered MSCs were found to be distributed only to the pleurae and the pleural cavity, providing a promising cell-based therapeutic strategy for primary and secondary pleural diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike classical intravenous or intratracheal delivery methods [5][6][7][8][9] , intrapleurally delivered MSCs were found to be distributed only to the pleurae and the pleural cavity, providing a promising cell-based therapeutic strategy for primary and secondary pleural diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, including one of our previous studies, have demonstrated that intravenous (iv) or intratracheal (it) delivery of bone marrow-derived mesenchymal stem cells (MSCs) participates in the improvement of various experimental models of lung injury, thus demonstrating that MSCs play an important role in the treatment of animals with acute lung injury [5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, intravenous MSC administration reduced lung inflammation and prolonged survival in a murine model of bleomycin-induced lung injury and fibrosis (Ortiz et al, 2003;Rojas et al, 2005). Similar effects of MSC treatment have been described in murine models of endotoxin-induced lung injury Xu et al, 2007;Xu et al, 2008). Xu et al observed that intravenous MSC administration prevents endotoxin-induced lung injury, edema formation and inflammation in mice (Xu et al, 2007).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 73%
“…Xu et al observed that intravenous MSC administration prevents endotoxin-induced lung injury, edema formation and inflammation in mice (Xu et al, 2007). Moreover, genetic engineering of MSCs showed to improve the protective effects of MSCs even more Xu et al, 2008). Mei et al evaluated the integrity of the alveolarcapillary membrane barrier by measuring total protein, albumin and IgM concentration in BALf in a murine model of LPS-induced ALI .…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…So, the results obtained and reported have been evaluated more carefully by some authors, who challenge the accuracy of the employed detection techniques. For example, after transplanting MSC GFP + in mice which had previously received an LPS intraperitoneal injection, Xu et al (2008) did not find, in the immunohistochemistry analysis of the pulmonary tissue conducted 14 days after the transplant, circumstantial evidence for a significant presence of cells with positive sign of GFP. However, although the authors did not find evidence for an actual integration of MSC to the pulmonary tissue and the presence of cells with the pulmonary phenotype, there was demonstration that the SC transplant afforded a decrease in the lungs inflammation and edema induced by the LPS.…”
Section: Stem Cells and Cell Therapy: The Rationale For Use In The Lungmentioning
confidence: 97%